PEMBENTUKAN KADER ANAK SEKOLAH DASAR: LITTLE NURSE DI SDN 02 BANGETAYU WETAN KECAMATAN GENUK KOTA SEMARANG - Nutrisia Nu’im Haiya; Dyah Wiji Puspitasari; Wahid Hasyim Alkanda; Adina Adelina; Nana Andriana; Misnawati Misnawati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
School Health Enterprises (UKS) is a business programmed by the government in improving public health, especially school children. UKS in implementing the work program under the guidance and supervision of Puskesmas. This requires a fairly good participation, which requires the Puskesmas to instill school cadres, so that community participation can run optimally, in this case the school community. The purpose of this program is to form a cadre of schoolchild with the name of Little Nurse to monitor the health development of school children in SDN 02 Bangetayu Wetan. The method used in fostering the participation of school students in improving school health through cadre selection, training and the formation of schoolchildren cadre, then named Little Nurse. Little Nurse is formed with 26 elementary school students consisting of grades 4 and 5. After being trained with some basic materials, little nurse members are inaugurated by the Head of Puskesmas. And furthermore work under the direction and supervision of Bangetayu Health Center, which can be further guidance by puskesmas or subsequent service program.Keywords: Little Nurse, Kader Anak Sekolah, School Health Enterprises (UKS)